Acute respiratory infections among under five children in a rural area of Kancheepuram district, Tamil Nadu, India: a cross-sectional study - A. K., Savitha; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2018)
Background: Acute respiratory infection (ARI) is an infection of the respiratory tract that may interfere with normal breathing. ARI is one of the leading causes of illness and death among children worldwide. The aim of the study was to estimate the prevalence of ARI among under 5 children in the rural field practice area of a medical college in Kancheepuram district of Tamil Nadu. Methods: This study is a community based cross–sectional study. The study population was children below five years of age and informant was the mother of the child. The sample size is 380 and simple random sampling method was used. Data was analyzed using the SPSS software, version 16, and presented as descriptive statistics. Results: The prevalence of ARI among children was 41.6%. Regarding the symptoms of ARI, 36.6% of them had either cold or runny nose, 27.9% had cough, 23.4% had stridor, 20.8% had reduced intake of food, 2.6% had either ear pain or discharge, 2.6% had rapid breathing.1.3% had wheeze, 0.8% were tired/drowsy, 0.5% had throat pain, 0.5% had convulsions and 17.1% of them had symptoms with fever. Conclusions: This study shows the prevalence of ARI among children below 5 years of age is 41.6% which is relatively high. The symptoms of ARI reflect the non severe form of pneumonia. More hospital based studies should be done in order to know the burden of severe form of pneumonia which contributes to the morbidity and mortality of children below five years of age.